2015
DOI: 10.1002/humu.22784
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-FunctionFANCLMutations Associate with Severe Fanconi Anemia Overlapping the VACTERL Association

Abstract: The diagnosis of VACTERL syndrome can be elusive, especially in the prenatal life, due to the presence of malformations that overlap those present in other genetic conditions, including the Fanconi anemia (FA). We report on three VACTERL cases within two families, where the two who arrived to be born died shortly after birth due to severe organs' malformations. The suspicion of VACTERL association was based on prenatal ultrasound assessment and postnatal features. Subsequent chromosome breakage analysis sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…Patients with a few of the very rare FA genotypes were reported to have VACTERL‐H as well as other FA‐associated birth defects (e.g., FANCI , FANCJ , and FANCB ) [Mikat et al, ; Savage et al, ; Vetro et al, ]. However, patients with other genotypes also have VACTERL‐H features, and thus the data are too few to state that a patient with FA who has VACTERL‐H will have a specific genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a few of the very rare FA genotypes were reported to have VACTERL‐H as well as other FA‐associated birth defects (e.g., FANCI , FANCJ , and FANCB ) [Mikat et al, ; Savage et al, ; Vetro et al, ]. However, patients with other genotypes also have VACTERL‐H features, and thus the data are too few to state that a patient with FA who has VACTERL‐H will have a specific genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Faivre et al reviewed data from questionnaires sent to representatives from 24 different countries, while Alter and Rosenberg reviewed cases described in previous reports in the medical literature. Small studies have reported extremely high rates of VACTERL‐H in patients with mutations in FANCI or FANCL [Savage et al, ; Vetro et al, ], and a boy with a mutation in FANCB [Mikat et al, ]. There is no systematic prospective study to date.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA (~3 μg) was extracted from peripheral blood samples, by using the QIAamp DNA Blood Mini Kit (Qiagen, Hilden, Germany). Library preparation was performed as previously reported [32] by using the SureSelect Human All Exon v5 target enrichment kit (Agilent Technologies). Sequencing was performed on HiSeq 2500 by using a Paired-End 100 bp protocol (Illumina, San Diego, CA, USA).…”
Section: Whole Exome Sequencing (Wes)mentioning
confidence: 99%
“…The human homologue of the FANCL gene has been found to be associated to the Fanconi anaemia, that is a genetically heterogeneous recessive disorder described by cytogenetic instability, hypersensitivity to DNA crosslinking agents, augmented chromosomal breakage, and defective DNA repair (Vetro et al 2015;Ceccaldi et al 2016). Interestingly, two SNPs located close to the human FANCL gene on Human Chromosome 2 (rs75575209 and rs11682175) have been found to be associated to Schizophrenia in a multi stage genome wide association study conducted on 36,989 cases and 113,075 controls (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014).…”
Section: Genome Wide Association Analysismentioning
confidence: 99%